2020
DOI: 10.4018/ijepr.2020040101
|View full text |Cite
|
Sign up to set email alerts
|

Communication-Oriented and Process-Sensitive Planning Support

Abstract: The complexity of the planning context has raised criticism against public participation for being a rigid top-down endeavour which does not recognize the different communicative needs and necessary working modes in the engagement of broad publics and collaborative small groups. Consequently, the problem is how to improve public participation so that it becomes more sensitive to the variety of communicative activities and knowledge needs involved in the design of urban planning processes. The aim of the articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 25 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…With regard to research in connection to practice, we identified an increasing mutual attunement of application, governance and instrumentation within the specifics of the particular context. A very good example of this is the strategic planmaking for the Finnish capital of Helsinki, in which a lot of technological instruments have been applied in very close cooperation with dedicated collaborative governance practices to arrive at policy recommendations for the sustainable future development of the city (see Staffans et al, 2020a). Still, our view is that much more frequent and widespread and explicit mutual attunement is needed to be better able to show that PSS really do add value in practice (Pelzer et al, 2014;Te Br€ oemmelstroet, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to research in connection to practice, we identified an increasing mutual attunement of application, governance and instrumentation within the specifics of the particular context. A very good example of this is the strategic planmaking for the Finnish capital of Helsinki, in which a lot of technological instruments have been applied in very close cooperation with dedicated collaborative governance practices to arrive at policy recommendations for the sustainable future development of the city (see Staffans et al, 2020a). Still, our view is that much more frequent and widespread and explicit mutual attunement is needed to be better able to show that PSS really do add value in practice (Pelzer et al, 2014;Te Br€ oemmelstroet, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous studies show that it is also possible to apply planning support tools to assist planning tasks in other phases (e.g. Geertman and Stillwell, 2020;Staffans et al, 2020). According to Kahila-Tani (2015), different kinds of Public Participation GIS (PPGIS) tools are required to support specific tasks in different planning phases, such as collecting data in the phase of early initiation, and obtaining participants' comments in a map in the phase of formulating alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the potential of digital tools especially PSS in solving these problems (e.g. Geertman and Stillwell, 2020; Kahila-Tani et al., 2015; Staffans et al., 2020). This research will contribute to link collaborative planning and PPScience by developing an evaluation framework and conducting empirical research in the Dutch context.…”
Section: Discussionmentioning
confidence: 99%
“…SoftGIS methods, for example, excel in capturing localized experiential knowledge for statistical analysis and systematic GIS (see Kahila and Kytt€ a, 2009). Next to SoftGIS methods, which produce divergent knowledge about an area from many individuals, methods are needed for rapid brainstorming from diverse small groups in a workshop setting as a foundation of divergent knowledge for further planning phases and planning support (Champlin, 2019;Staffans et al, 2020).…”
Section: Requirement 2 Representation Of Both the Expertise Of Planni...mentioning
confidence: 99%
“…When planning is in its early stages, divergence and shared learning about the system is more the focus than converging and decision making (te Brömmelstroet, 2017a). Staffans et al (2020) outline two types of knowledge divergence that should be supported in multi-actor planning processes. The first is the production of diverse data, ideas, and information sourced through large-scale participation of the broader public.…”
Section: Operationalization Of Key Termsmentioning
confidence: 99%